Modern weapons and military equipment for issue 3-2015 - Ostojić, Nikola M.; Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Glory and power of Russian weaponry at the parade commemorating the 70th anniversary of Victory Day